2009
DOI: 10.1186/1472-6750-9-17
|View full text |Cite
|
Sign up to set email alerts
|

The properties of bioengineered chondrocyte sheets for cartilage regeneration

Abstract: Background: Although the clinical results of autologous chondrocyte implantation for articular cartilage defects have recently improved as a result of advanced techniques based on tissue engineering procedures, problems with cell handling and scaffold imperfections remain to be solved. A new cell-sheet technique has been developed, and is potentially able to overcome these obstacles. Chondrocyte sheets applicable to cartilage regeneration can be prepared with this cellsheet technique using temperature-responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 24 publications
2
71
0
Order By: Relevance
“…Mitani et al investigated the properties of chondrocyte sheets and showed that expression of Sox 9, collagen type 2 and 27, integrin a10, and fibronectin were higher in layered chondrocyte sheets than in a single chondrocyte sheet in vitro. 21 In addition, Hamahashi et al showed that layered chondrocyte sheets produced higher levels of TGFb and PGE2 as humoral factors compared with monolayer chondrocyte sheets and suspected that these factors might contribute to cartilage repair. 22 However, these previously reported results might not…”
Section: Discussionmentioning
confidence: 99%
“…Mitani et al investigated the properties of chondrocyte sheets and showed that expression of Sox 9, collagen type 2 and 27, integrin a10, and fibronectin were higher in layered chondrocyte sheets than in a single chondrocyte sheet in vitro. 21 In addition, Hamahashi et al showed that layered chondrocyte sheets produced higher levels of TGFb and PGE2 as humoral factors compared with monolayer chondrocyte sheets and suspected that these factors might contribute to cartilage repair. 22 However, these previously reported results might not…”
Section: Discussionmentioning
confidence: 99%
“…However, this study did not discuss the related indexes of the scaffold. In subsequent studies, we will assess new scaffold materials, electrostatic spinning (Agarwal et al, 2008;Janjanin et al, 2008;Wright et al, 2010), and cell-chip technology (Kaneshiro et al, 2006;Mitani et al, 2009;Tani et al, 2010;Weder et al, 2010), and in more detail compare the properties of the engineered cartilages with normal cartilages.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, piezoelectric materials are being widely adapted for use as scaffolds for tissue regeneration and repair applications and have even been shown to influence gene expression in the case of cartilaginous implants utilizing the piezoelectric polymer polyvinylidene fluoride (PVDF). 49,50 Fibroblasts grown on piezoelectrically-activated (presenting charge on surface) implants show enhanced migration, adhesion and secretion and the implants themselves showed higher fibrosis levels in rats in vivo, illustrating wound healing capabilities. 51 However, in order to elucidate the fundamental basis for the observed improved cellular function due to charge, synthetic biology techniques can be employed.…”
Section: Effect Of Substrate Stiffnessmentioning
confidence: 99%